Comparative assessment of fully laparoscopic Duhamel-Z with minimal rectorectal dissection vs. laparoscopy-assisted Duhamel-Z with blunt manual rectorectal dissection for total colonic aganglionosis - Miyano, Go; Iida, Hisae; Ebata, Yu; Abe, Eri; Kato, Haruki; Mikami, Takafumi; Ishii, Junya; Lane, Geoffrey J.; Yamataka, Atsuyuki; Okazaki, Tadaharu (Frontiers in Pediatrics, 2023)
Aims: Early postoperative outcome (EPO) was compared between fully laparoscopic Duhamel-Z (F-Dz) and laparoscopy-assisted Duhamel-Z (A-Dz) anastomoses performed for total colonic aganglionosis (TCA). Methods: EPO was assessed quarterly for the first year after F-Dz/A-Dz using a continence evaluation score (CES) based on stool frequency (motions/day) and stool consistency (0=liquid, 1=soft, 2=formed), presence of anal erosion (0=severe, 1=moderate, 2=mild), and incidence of enterocolitis. Surgical technique involved taking the ileostomy down, dissecting the colon laparoscopically, and preparing the pull-through ileum through the stoma wound. In F-Dz (n=3), a working port (SILS trocar) was inserted, and laparoscopic retrorectal dissection with forceps used to create a retrorectal tunnel from the peritoneal reflection extending downward as narrow as possible along the posterior wall of the rectum to prevent lateral nerve injury and preserve vascularity. After completing the tunnel, the ileum was pulled-through from an incision on the anorectal line and a Z-shaped ileorectal side-to-side anastomosis performed without a blind pouch. In A-Dz (n=11), the retrorectal pull-through route was created through a Pfannenstiel incision using blunt manual (finger) dissection along the anterior surface of the sacrum. Results: Subject backgrounds were similar. Mean quarterly data were: frequency (F-Dz: 4.67, 4.67, 4.67, 3.33) versus (A-Dz: 7.27, 7.09, 6.18, 5.36) p<.05; consistency (F-Dz: 0.33, 0.67, 0.67, 0.67) versus (A-Dz: 0.27, 0.45, 0.70, 0.73) p=ns; anal erosion (F-Dz: 0.33, 0.33, 0.33, 0.67) versus (A-Dz: 0.18, 0.36, 0.45, 0.64) p=ns; and enterocolitis (F-Dz: 1 episode in 1/3 cases or 33.3%) versus (A-Dz: 7 episodes in 6/11 cases or 54.5%) p=ns. Conclusions: Overall, EPO after F-Dz was better than after A-Dz.